Association Between Oral Health and Gastric Cancer in Korean Adults - Sang Hoon Lee; Hyunseok Cho; Sung Chul Park; Sang Hoon Kim; Seung Young Kim; Han Jo Jeon; Sang Pyo Lee; Younghee Choe; the Metabolism, Obesity, and Nutrition Research Group of the Korean College of Helicobacter and Upper Gastrointestinal Research (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Poor oral hygiene is known to be associated with gastric cancer, but this remains controversial. In this study, we investigated the association between oral health and gastric cancer in Korean adults using data from the Korea National Health and Nutrition Examination Survey. Methods We analyzed data of 79501 patients with gastric cancer and 41856805 individuals without gastric cancer (control group) using the 7th and 8th Korea National Health and Nutrition Examination Survey (2016–2019) records. Layer and colony variables and weights were used for the complex sample design. We performed logistic regression analysis of complex samples to analyze factors that affect gastric cancer development. Results Patients with gastric cancer were older and had a higher prevalence of hypertension, hyperlipidemia, and diabetes and a higher rate of current smoking and alcohol consumption than individuals without gastric cancer (p<0.001). Regarding oral health-related factors, the prevalence of very uncomfortable chewing difficulty was significantly higher in patients with gastric cancer (14.4% vs. 3.6%, p<0.001). On multivariate analysis of factors associated with gastric cancer, chewing difficulty showed the highest odds ratio (5.351, 95% confidence interval 2.128–8.982). Patients with very uncomfortable chewing difficulty had high rates of previous dental nerve treatment, gum disease treatment, tooth extraction or intraoral surgery, and prosthetic repair (p<0.001). Conclusions Oral health-related chewing difficulties were associated with gastric cancer, which may be attributable to poor oral hygiene and degradation of oral microbiota. Patients at risk of gastric cancer warrant timely medical interventions to address their oral health and chewing difficulties.